Answer:
6x^2 -2x
Step-by-step explanation:
As written, the constant terms in the first factor cancel each other. The distributive property is used to perform the multiplication:
(3x^2 +1 -1 -x)(2) = (3x^2 -x)(2) = (3x^2)(2) -x(2)
= 6x^2 -2x
Answer:
B. The Huddle Room, by 3 square feet
Step-by-step explanation:
9 * 11 = 99
8 * 12 = 96
99 - 96 = 3
The Huddle Room, by 3 square feet
Hope this helps!
Answer:
SA = 2400 cm²
Step-by-step explanation:
SA of a cube = S² x 6 (the number of its faces)
SA = 20² x 6
SA = 400 x 6
SA = 2400 cm²